LEGAL PROTECTION OF OUTSOURCING LABOR COMPANIES IN MEDAN CITY - Lenny Mutiara Ambarita; Pasu Malau (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The legalization of outsourcing raises the problem of sociological enactment which is based on the effectiveness of law, where the basis of law is based on acceptance or recognition by those to whom the law is aimed, considering that the legalization of outsourcing is rejected by the majority of the community, especially those who work in companies. The approach method used is Normative Legal Research (normative juridical) by using the statutory regulatory approach, and empirical research (field data). The data analysis was carried out qualitatively to look for dominant factors that have potential or trends in legal protection for labor workers, which have recently become guidance material based on Law No. 13 of 2003 concerning manpower. The results of the study can be argued that various legal protections for workers based on Law no. 13 of 2003, there are 3 (three) types of protection for workers / laborers, respectively: Economic protection, namely protection of workers in the form of sufficient income, including if the worker is unable to work against his will. Social protection, namely labor protection in the form of occupational health insurance, and freedom of association and protection of the right to organize. Technical protection, namely protection of workers in the form of work security and safety The implementation of work protection and work conditions such as requirements for employment relationships, requirements for wages, requirements for work time breaks and wages for overtime work, requirements for social security, compensation for work accidents, and safety and health requirements for outsourced workers / laborers in Medan City are still not provided in accordance with the prevailing laws and regulations, so that workers feel disadvantaged economically and socially, feel that they are treated unfairly and inhumanely before, during and after they work.